Tissue engineering and surgery: from translational studies to human trials - Vranckx Jan Jeroen; Hondt Margot Den (Innovative Surgical Sciences, 2017)
Tissue engineering was introduced as an innovative and promising field in the mid-1980s. The capacity of cells to migrate and proliferate in growth-inducing medium induced great expectancies on generating custom-shaped bioconstructs for tissue regeneration. Tissue engineering represents a unique multidisciplinary translational forum where the principles of biomaterial engineering, the molecular biology of cells and genes, and the clinical sciences of reconstruction would interact intensively through the combined efforts of scientists, engineers, and clinicians. The anticipated possibilities of cell engineering, matrix development, and growth factor therapies are extensive and would largely expand our clinical reconstructive armamentarium. Application of proangiogenic proteins may stimulate wound repair, restore avascular wound beds, or reverse hypoxia in flaps. Autologous cells procured from biopsies may generate an ‘autologous’ dermal and epidermal laminated cover on extensive burn wounds. Three-dimensional printing may generate ‘custom-made’ preshaped scaffolds – shaped as a nose, an ear, or a mandible – in which these cells can be seeded. The paucity of optimal donor tissues may be solved with off-the-shelf tissues using tissue engineering strategies. However, despite the expectations, the speed of translation of in vitro tissue engineering sciences into clinical reality is very slow due to the intrinsic complexity of human tissues. This review focuses on the transition from translational protocols towards current clinical applications of tissue engineering strategies in surgery.